Impact of Fetuin-A on progression of calcific aortic valve stenosis - The COFRASA - GENERAC study. (15th August 2018) - Kubota, Naozumi; Testuz, Arianne; Boutten, Anne; Robert, Tiphaine; Codogno, Isabelle; Duval, Xavier; Tubiana, Sarah; Hekimian, Guillaume; Arangalage, Dimitri; Cimadevilla, Claire; Kerneis, Caroline; Vahanian, Alec; et al.
Abstract: Background: Aortic stenosis (AS) is an active disease, but the determinants of AS progression remain largely unknown. Low levels of Fetuin-A, a powerful inhibitor of ectopic calcification, have been linked to ectopic calcium tissue deposition but its role in AS progression has not been clearly evaluated. Methods: In our ongoing prospective cohort (COFRASA/GENERAC), serum Fetuin-A level was measured at baseline and AS severity was evaluated at baseline and yearly thereafter using echocardiography (mean pressure gradient (MPG)) and computed tomography (degree of aortic valve calcification (AVC)). Annual progression was calculated as [(final measurement-baseline measurement)/follow-up duration] for both MPG and AVC measurements. Results: We enrolled 296 patients (74 ± 10 years, 73% men); mean follow-up duration was 3.0 ± 1.7 years. No correlation was found between baseline serum Fetuin-A (0.55 ± 0.15 g/L) and baseline AS severity (r = 0.25, p = 0.87 for MPG; r = 0.06, p = 0.36 for AVC). More importantly, there was no correlation between baseline serum Fetuin-A level and AS progression either assessed using MPG or AVC (both r = 0.01, p = 0.82). In bivariate analysis, after adjustment for age, gender, baseline AS severity, or valve anatomy, Fetuin-A was not associated with AS progression (all p > 0.20). The absence of link with AS progression was further confirmed by the absence of link betwen serum Fetuin-A and the occurrence of AS-related events (p = 0.17). Conclusions: In a large prospective cohort of AS patients, serum Fetuin-A was not associated to hemodynamic or anatomic AS progression. Despite its capacity to inhibit ectopic calcium deposition, Fetuin-A serum level seemed to have minor influence on AS progression. Highlights: Fetuin-A is a powerful inhibitor of ectopic calcification but its role in the progression of aortic valve stenosis (AS) has not been clearly evaluated. Serum Fetuin-A at study entry (0.55 ± 0.15 g/L) was not correlated to severity of aortic stenosis evaluated either by echocardiography (mean pressure gradient (MPG), r = 0.25, p = 0.87) or my scanner (degree of aortic valve calcification (AVC), r = 0.06, p = 0.36). In univariate or multivariate analysis (adjustment for age, gender, baseline AS severity, or valve anatomy), serum Fetuin-A level was not associated with AS progression. Serum Fetuin-A was not predictive of the occurrence of AS-related events (p = 0.17).